The throwing shoulder: Part 1. A review of the functional anatomy of the shoulder (Journal of Australian Strength and Conditioning, 2012)
The action of throwing is a full body involvement, where the goal is the successful transfer of lower body generated force through to the hand to maximise ball velocity. The ability of the shoulder girdle to perform this action, given the magnitude of mobility at the glenohumeral joint is accomplished by many structures - static and dynamic. The capability for the shoulder to move through range either under load or with high velocity is due to an intricate coordination of muscles acting on the scapula and humerus, delicately altering muscle lengths and forces to achieve glenohumeral stability. This coordination is controlled by constant neural information provided by several specialised structures within the muscles, tendons and ligaments of the shoulder girdle. Injury prevention and rehabilitation of the shoulder requires knowledge of anatomical adaptations and function to be successful, and attention to the balance of muscular strength, flexibility and endurance of scapular stabilisers and the rotator cuff. Strength and conditioning coaches working with throwing (and overhead athletes) can reduce injury risk by monitoring of throwing technique and volume, particularly in the developing athlete and incorporating shoulder injury prevention strategies into resistance training programs. Interventions include assessment of shoulder flexibility, and the strength and muscle balance of the rotator cuff and scapular stabilisers. The purpose of this paper is to review the functional anatomy of the shoulder in order to better understand the glenohumeral adaptations to throwing and the rationale for injury prevention and rehabilitation programs.